Intervensi Family Triple Support (FTS) Berpengaruh terhadap Respon Bayi pada saat Imunisasi DPT - Padila, Padila; Andri, Juli; Andrianto, Muhammad Bagus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine whether the FTS intervention affects the baby's pain response when DPT immunization is given at the Community Health Center. This type of research is pre-experimental with a one-group pretest-posttest design. The results of the study showed that the frequency of responses to pain in babies before treatment was the highest, namely seven babies with a pain scale of 3, a percentage of 46.7% in the moderate pain category, the frequency of responses to pain in babies after treatment was the highest, six babies with a pain scale of 2, percentage 40% with the mild category. At the same time, the results of the bivariate analysis show that the p-value is 0.000 < 0. In conclusion, family triple support intervention has a significant effect on the baby's pain response when DPT immunization is given at the Community Health Center. Keywords: Family Triple Support, DPT Immunization, Baby Response